An audio encryption based on synchronization of robust BAM FCNNs with time delays - Kalpana, Muthusamy; Ratnavelu, Kurunathan; Balasubramaniam, Pagavathi (Springer, 2019)
In this work, authors’ proposed an audio encryption based on synchronization of hybrid bidirectional associative memory (BAM) and fuzzy cellular neural networks (FCNNs) with time delays. Here, the significant effort is to find the values of the parameters A,B,D,α,β,Ã,B~,D~,α~,β~,L,L~,Od,Õd,Oa,Õa,Ob,Õb, of the given robust BAM FCNNs system to obtain the dynamical signal (chaotic) which are used to encrypt an audio file and satisfy the condition of Linear matrix inequality (LMI) by choosing suitable Lyapunov-Krasovskii functional (LKF). Further, the key sensitivity of order 1 0 − 10 of this proposed method have massive key space to make brute-force attack infeasible. Numerical simulations, results and discussions along with comparison are provided to illustrate the effectiveness and merits of the proposed scheme. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.